Syphilitic optic neuritis and uveitis – case report - Bonińska, Karolina; Sobutka, Hanna; Mrowicka, Dagmara; Post, Michał; Dybek, Tomasz; Bednarski, Maciej; Cisiecki, Sławomir (Klinika Oczna / Acta Ophthalmologica Polonica, 2024)
We report the case of a 34-year-old male patient who presented to the Ophthalmology Department because of a decline in visual acuity in both eyes. The patient was diagnosed with anterior and posterior uveitis in the right eye and optic neuritis in the left eye, secondary to syphilis. Topical and systemic treatments were implemented, leading to a gradual improvement in the patient’s condition. Considering the rising global incidence of syphilis and the non-specific ocular manifestations it may present, the diagnosis should be considered in patients with ocular inflammatory conditions of unknown etiology.